Estimating trade policy effects with structural gravity - Roberta Piermartini; Yoto V. Yotov (World Trade Organization (WTO), 2016)
The objective of this manuscript is to serve as a practical guide for estimations with the structural gravity model. After a brief review of the theoretical foundations, we summarize the main challenges with gravity estimations and we review the solutions to address those challenges. Then, we integrate the latest developments in the empirical gravity literature and we offer six recommendations to obtain reliable partial equilibrium estimates of the effects of bilateral and non-discriminatory trade policies within the same comprehensive, and theoretically-consistent econometric specification. Our recommendations apply equally to analyses with aggregate and disaggregated data. Interpretation, consistent aggregation methods, and data challenges and sources for gravity estimations are discussed as well. Empirical exercises demonstrate the usefulness, validity, and applicability of our methods.
Keywords: F13; F14; F16; 330; Structural Gravity; Trade Policy; Estimation; Partial Equilibrium Analysis